2014
DOI: 10.4028/www.scientific.net/amr.996.694
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Interpass Rolling of Wire + Arc Additively Manufactured Titanium Components

Abstract: Abstract. Wire + Arc Additively Manufactured components contain significant residual stresses that manifest in distortion. Each layer of an additively manufactured wall was rolled with the aim of reducing the residual stress. Neutron diffraction and contour method measurements show that the residual stresses were reduced -particularly at the boundary with the substrate. The process also reduced distortion, and refined the microstructure which may facilitate implementation on aerospace components. IntroductionA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 12 publications
(26 reference statements)
5
43
2
1
Order By: Relevance
“…[8] When applied to steel WAAM structures, rolling resulted in a reduction of the grain size, due to the enhanced recrystallization that occurred with the deposition of the subsequent layer on the plastically deformed component. [9] Rolling of Ti-6Al-4V WAAM structures was initially presented, [10,11] and will be discussed in depth in this paper.…”
Section: Additive Manufacturing (Am) Is a Fabricationmentioning
confidence: 99%
“…[8] When applied to steel WAAM structures, rolling resulted in a reduction of the grain size, due to the enhanced recrystallization that occurred with the deposition of the subsequent layer on the plastically deformed component. [9] Rolling of Ti-6Al-4V WAAM structures was initially presented, [10,11] and will be discussed in depth in this paper.…”
Section: Additive Manufacturing (Am) Is a Fabricationmentioning
confidence: 99%
“…Although WAAM Ti-6Al-4V seldom contains process-induced defects, studies have shown that feedstock contamination can be a common source for occurrence of gas pores [5,17]. Recent advances on the application of in-situ rolling [18] and inter-pass rolling techniques [19,20] have shown promising results in homogenising the microstructure by making the prior β grains equiaxed and more importantly, eliminating the process-induced defects in the build stage. However, adding a processing step significantly increases the production time and cost.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction for the next 20 years is that aircraft industry will need over 18 million tons of titanium wherein the buy-to-fly ratio is 5. This means that 72 million tons of titanium will be a waste material [5][6][7][8].…”
Section: Povzetekmentioning
confidence: 99%